KRITIK TAFSIR TEOLOGIS DALAM PERDEBATAN IMAMAH: Analisis atas Ayat Mawaddah, Wilayah dan Tathhir antara Ibn Taimiyyah dan Ibn al-Muthahhar - M. Minanur Rohman (Al-Nizam: Indonesian Journal of Research and Community Service, 2026)
This study aims to comparatively analyze the interpretations of Ibn al-Muthahhar al-Hilli and the critiques of Ibn Taymiyyah regarding three theological verses in the Qur'an: the verse of mawaddah (Qur'an 42:23), the verse of wilayah (Qur'an 5:55), and the verse of tathhir (Qur'an 33:33). This research employs a qualitative approach based on library research, integrating comparative exegesis analysis and argumentation theory, particularly Stephen Toulmin’s model. The findings indicate that Ibn al-Muthahhar al-Hilli constructs his interpretations by integrating Qur'anic text, hadith reports, and theological inference to support the doctrine of imamah, while Ibn Taymiyyah offers systematic critiques through evaluating the validity of narrations, linguistic analysis, and restricting textual meaning. From an argumentative perspective, the main weakness in al-Hilli’s construction lies in the inferential link between evidence and claims, which is not always strong, whereas Ibn Taymiyyah’s strength lies in his ability to critique both the data and the basis of inference. However, Ibn Taymiyyah’s approach also demonstrates a restrictive tendency that limits broader theological interpretations. This study concludes that the debate between the two figures reflects a fundamental difference in hermeneutical paradigms: one emphasizing theological coherence and the other emphasizing epistemic caution. These findings contribute to the study of polemical exegesis and argumentation analysis within the Islamic intellectual tradition.